Empowering India’s Youth: A Critical Analysis of NEP 2020's Implementation Strategies - Kumar, Santosh (AG Volumes, 2025)
India is actively implementing the guidelines of the National Education Policy 2020 (NEP 2020) to bring transformative changes in school and higher education. The policy aims to create an education system that empowers youth with knowledge, skills, and human values, equipping them to tackle present and future societal challenges through innovation and technological proficiency. NEP 2020 emphasizes a holistic learning approach, fostering critical thinking and problem-solving abilities to build a self-reliant and globally competitive workforce. In higher education, the policy focuses on multidisciplinary, autonomous institutions offering undergraduate, postgraduate, and research programs, guided by skilled educators committed to academic excellence. It encourages the integration of technology, interdisciplinary learning, and value-based education to promote societal progress. Effective implementation strategies include forming competent committees, enforcing balanced regulations, ensuring transparency, and adopting performance-based faculty evaluations. Measures such as a "publish or perish" culture, periodic institutional audits through accreditation bodies like National Accreditation Council (NAC), and strict accountability mechanisms are crucial for success. If executed systematically, NEP 2020 has the potential to establish an inclusive, innovative, and technologically advanced education system that prepares India’s youth for global challenges and opportunities.